A profile of the mental health needs of children in out-of-home care in Wales between 2019-2020 - Cummings, Aimee (International Journal of Population Data Science, 2024)
Objective and approach Young people who have experience of being in out-of-home care are more likely to have poorer mental health when compared to those in the general population. However, some of the most highly cited literature around prevalence rates of different mental health conditions are becoming outdated. Data held in the Secure Anonymised Information Linkage (SAIL) Databank was used to better understand the mental health needs of this group. Health data from General Practitioner records, emergency department, and inpatient admissions were linked to the 2019/20 data from children’s social services. Results Mental health was considered in relation to two facets: indicators and conditions. Indicators included incidents of self-harm, drug or alcohol use, while conditions included symptoms or diagnoses of five different mental health conditions (anxiety, depression, eating disorder, conduct disorder, and severe mental illnesses). Prevalence was looked at across general demographic characteristics, as well as those specific to the care experience. Logistic regression models examined if a young person’s care experience could predict the likelihood of mental health need. Conclusions The findings from this piece of work will inform current understanding of the vulnerabilities of this group. Future work will compare the needs of this group to others, including Children Receiving Care and Support, as well as the general population. Implications This work will provide an update to existing literature. The findings have the potential to contribute to discussions about how we best support this group and will inform approaches to meeting the health needs of care-experienced young people.